Determinants of switching intention from web-based stores to retail apps: Habit as a moderator. (May 2022) - Iranmanesh, Mohammad; Min, Connie Low; Senali, Madugoda Gunaratnege; Nikbin, Davoud; Foroughi, Behzad
Abstract: Online retailers seek to motivate their customers to switch from web-based stores to retail apps as using the latter as a shopping channel has many benefits for retailers compared to web-based stores. This study aims to examine the drivers of customers' intention to switch from web-based stores to retail apps by applying the Stimulus-Organism-Response (S–O-R) model. The moderating role of habit was investigated. Data were collected from 389 Malaysian individuals through an online survey and analysed using the partial least squares technique. The results indicated that performance expectancy has a significant influence on switching intention and is driven by mobile characteristics. Furthermore, effort expectancy has a positive effect on both performance expectancy and switching intention and is triggered by visual complexity and aesthetic quality. The moderating effects of habit on the associations between performance expectancy, effort expectancy and switching intention were not supported. The findings extend the literature on retail apps by exploring the switching intention drivers and testing the moderating effect of culture, which have received less attention. The results enable retail apps' developers and marketers to strategise retail apps development and marketing activities in a way that encourages current web-based stores' customers to use retail apps as a better alternative. Highlights: To identify the drivers of switching from web-based stores to retail apps. Performance expectancy is driven by mobile characteristics. Effort expectancy is triggered by visual complexity and aesthetic quality. Habit does not offset the influence of performance expectancy and effort expectancy on switching intention.